Konsep Multikulturalisme Dalam Al-Qur’an (Kajian Tafsir Tematik) - F, Firmansyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the critical study of the concept of multiculturalism in the Qur’an through an understanding of the essence of multiculturalism in the Qur’an, the existence of multiculturalism in the Qur’an, and the urgency of multiculturalism. This type of research is qualitative research using descriptive analysis methods. Data were obtained through library research, namely data collection by understanding and studying theories from various literature related to the research. The theories and literature can be in the form of books, journals, previous research results, important documents or notes and other literature sources related to the concept of multiculturalism in the Qur’an. This study uses the tafsīr mauḍūi’ method (thematic interpretation), which is a method used by collecting verses of the Qur’an from various surahs and those related to previously determined issues or topics, then the interpreter discusses and analyzes the contents of the verses so that they become a whole unit. The thematic research used in this study is conceptual thematic, namely research on certain concepts that are not explicitly mentioned in the Qur’an, but substantially the idea of the concept is found in the Qur’an. The results of this study indicate that multiculturalism is a social order recognized in Islam as part of the sunnatullah, which makes the diversity of tribes, nations, languages, and cultures a means to build harmonious interactions, with the principles of equality, justice, brotherhood, and tolerance based on the values of the Qur’an. This study has broad implications, both in theological, social, and academic realms. Theologically, this study confirms that the Qur’an recognizes diversity as a sunnatullah that cannot be denied. Plurality in human life is not just a social phenomenon, but part of the Divine will that aims for humans to know each other (li ta’ārafu) and build a harmonious life.